Psychological Technique to Reduce the Psychological Illness of Athletes - Ravindra Ghoti; Aprana Astputre (MultiTech Publisher, 2023)
The present study has been conducted to investigate the Psychological Techniques to reduce the psychological illness of athletes. Study includes the athletes (Distract level players) in Aurangabad respectively who were between the age of 20 and 30. To assess the Anxiety and Frustration and factors of the subject the Shina’s Anxiety inventory and Nayrashmapa Frustration test and Psychological Techniques is counseling and Guidance, Meditation, and Relaxations techniques. Research design is Pre-Post test. Proposed Statistical Procedure is Descriptive statistics i.e. Mean, S.D, will be computed and‘t’ test .Conclusion in this study On the basis of data and discussion of results, the hypotheses were tested and verified. Psychological illness of athletes tends to show reduced by Psychological techniques.